2019
DOI: 10.1101/742676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Megakaryocytes Display Innate Immune Cell Functions and Respond during Sepsis

Abstract: 24 Megakaryocytes (MKs) are precursors to platelets, the second most abundant cells in the 25 peripheral circulation. However, while platelets are known participate in immune responses and 26 play significant roles during infections, the role of MKs within the immune system has not been 27 explored. Here we utilize in vitro techniques to show that both cord blood-derived MKs (CB 28 MKs) and MKs from a human megakaryoblastic leukemia cell line (Meg-01) chemotax towards 29 pathogenic stimuli, phagocytose bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…23 However, Frydman et al have shown that megakaryocytes can generate histone-decorated chromatin webs, which mimics the NETs. 10 This report also demonstrated increased CD61þ staining in the kidneys and lungs from patients with sepsis, which correlated with the development of organ dysfunction, an accompaniment often present in ARDS.…”
Section: Lung Megakaryocytes and Acute Respiratory Distress Syndromesupporting
confidence: 60%
See 2 more Smart Citations
“…23 However, Frydman et al have shown that megakaryocytes can generate histone-decorated chromatin webs, which mimics the NETs. 10 This report also demonstrated increased CD61þ staining in the kidneys and lungs from patients with sepsis, which correlated with the development of organ dysfunction, an accompaniment often present in ARDS.…”
Section: Lung Megakaryocytes and Acute Respiratory Distress Syndromesupporting
confidence: 60%
“… 9 Surface adhesion molecules expressed on megakaryocytes can assist in retention of these cells in the lungs, particularly when the pulmonary endothelium is activated by inflammation or infection. 10 Megakaryocytes also phagocytose bacteria and viruses and use their lysosomal granules as pathogen-eradicating bullets. 10 11 12 An additional immune role for megakaryocytes is reflected by their interaction with neutrophils, which occurs through the unique process called “emperipolesis.” 13 During emperipolesis, these leukocytes are engulfed by the megakaryocytes with no membrane disruption but allowing cellular material transfer between the cells.…”
Section: Is There a Specific Role For The Pulmonary Megakaryocytes?mentioning
confidence: 99%
See 1 more Smart Citation